(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Introduction: Avascular necrosis (AVN) of femoral head is a dreadful and disabling condition. Total Hip Replacement (THR) is an effective solution. In this study we have analyzed the results of total hip replacement performed in ShSMCH, Dhaka for AVN of femoral head from July 2018 up to June 2020. Patients and Methods: In this prospective study, 19 total hip replacement were done. All patients were diagnosed as primary AVN of Ficat and Arlet Grade III and IV. Out of 19 patients, 15 patients operated with cementless pressfit implants and 4 patients with cemented implants. Results: Among the 19 patients 12 were male (63.15%) and 7 were female (36.85%). Mean age was 35.57 year. Operation done on right hip in 10 patients (52.63%) and on left hip 9 patients (47.37%). All the patients were evaluated pre-operatively and Harris Hip Score was poor ie, average 41.84. Three months post operatively Harris Hip Score improved significantly 47.36% patients value was 90-100 ie, excellent, 31.57% patients value was 80-90 ie, good and 21.05% patients value was 70-80 ie, fair. None documented as poor. In complication, 1 patient (5.26%) developed serous discharge which resolved with antibiotic treatment after culture and sensitivity. Conclusion: THR is the most effective method of removing pains and distress of end stage AVN of hip. J Shaheed Suhrawardy Med Coll 2020; 12(2): 87-89